Report of the Second Asian Prostate Cancer (A-CaP) Study Meeting - Choung Soo Kim (2018)
© 2017 The Asian Prostate Cancer (A-CaP) Study is an Asia-wide initiative that has been developed over the course of 2 years. The study was launched in December 2015 in Tokyo, Japan, and the participating countries and regions engaged in preparations for the study during the course of 2016, including patient registration and creation of databases for the purpose of the study. The Second A-CaP Meeting was held on September 8, 2016 in Seoul, Korea, with the participation of members and collaborators from 12 countries and regions. Under the study, each participating country or region will begin registration of newly diagnosed prostate cancer patients and conduct prognostic investigations. From the data gathered, common research themes will be identified, such as comparisons among Asian countries of background factors in newly diagnosed prostate cancer patients. This is the first Asia-wide study of prostate cancer and has developed from single country research efforts in this field, including in Japan and Korea. At the Second Meeting, participating countries and regions discussed the status of preparations and discussed various issues that are being faced. These issues include technical challenges in creating databases, promoting participation in each country or region, clarifying issues relating to data input, addressing institutional issues such as institutional review board requirements, and the need for dedicated data managers. The meeting was positioned as an opportunity to share information and address outstanding issues prior to the initiation of the study. In addition to A-CaP-specific discussions, a series of special lectures was also delivered as a means of providing international perspectives on the latest developments in prostate cancer and the use of databases and registration studies around the world.